2005
DOI: 10.1254/jphs.fp0050127
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Stress-Induced Brain Neurotransmitter Changes and the Effect of Ocimum sanctum (Linn) Treatment in Albino Rats

Abstract: Abstract. In this modern world, stress and pollution are unavoidable phenomena affecting the body system at various levels. A large number of people are exposed to potentially hazardous noise levels in daily modern life, such as noise from work environments, urban traffic, and household appliances. A variety of studies have suggested an association between noise exposure and the occurrence of disorders involving extra-auditory organs such as disorders of the nervous, endocrine, and cardiovascular systems. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 17 publications
0
79
0
2
Order By: Relevance
“…Noise exposure exceeds 90 dB has been reported to be a source of stressor [4]. The adverse impact of noise on learning, memory and hippocampal neurogenesis has been reported by previous studies [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 72%
“…Noise exposure exceeds 90 dB has been reported to be a source of stressor [4]. The adverse impact of noise on learning, memory and hippocampal neurogenesis has been reported by previous studies [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 72%
“…Moreover, alterations in brain monoamine neurotransmitter release are associated with brain injury and cognitive impairment 27) . Acute or sub-chronic noise exposures were both found to change the level of biogenic amines in discrete regions of the rat brain 17,26) . Our results demonstrat that the levels of DA, NE and 5-HT were significantly decreased in the hippocampi of young male rats after noise exposure (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…LM is coordinated among different brain regions, especially the hippocampus and the medial prefrontal cortex 12,15,16) . In Ravindran's study, rats were subjected to 100 dB broadband white noise for 15 days, which was found to alter the biogenic amine levels in discrete regions of the rat brain 17) . However, to date, there is very little information about the noiseinduced changes of monoamine neurotransmitter levels in the hippocampus and there are no studies on long-term monoamine level alterations after noise exposure in the literature.…”
mentioning
confidence: 99%
“…The noise can be set at a certain level (e.g., 100 dB or higher) and the animals can be exposed to the noise protocol either acutely or repeatedly (4 hours/day/15 days). 113,114 Like those of other protocols, the behavioral effects of noise stress can be observed in animal models of anxiety and depression.…”
Section: -112mentioning
confidence: 99%